Pirates Don't Take Baths - Segal, John (New York : Philomel Books, 2011)
A young pig tries to avoid taking a bath by claiming to be a variety of characters, from an astronaut to an Eskimo, as his mother tries to lure him into the tub.
Keywords: Baths -- Fiction; Pigs -- Fiction